Five new species and new records of caddisflies (Insecta: Trichoptera) from Australia’s ‘Top End’ - Cartwright, David I.; Dostine, Peter (Zootaxa, 2022)
Five new species of caddisflies are described from the ‘Top End’ of the Northern Territory, three in the family Ecnomidae—Ecnomina radonica sp. nov., Neboissomina topendica sp. nov., Wellsomina tamoides sp. nov.—and two in Polycentropodidae—Polyplectropus bamboosa sp. nov. and P. berryensis sp. nov. Four of these new species are endemic to the Top End, P. berryensis sp. nov. is also recorded from northern Western Australia. In addition, first reports are given for the Top End for two previously described species, one each in genera Ecnomus McLachlan and Wellsomina Cartwright, and new records are given for eighteen species of Ecnomus McLachlan, one further species of Ecnomina Kimmins and Neboissomina Cartwright, and six species of Wellsomina Cartwright (all Ecnomidae), four species of Nyctiophylax Brauer (Polycentropodidae), and Tinodes radona Neboiss (Psychomyiidae). Finally, one male (and three females) of Hyalopsyche disjuncta Neboiss (Dipseudopsidae) are recorded from the Northern Territory, the first adult specimens of this species found outside northeastern Queensland.